Equating by Using Circle Equation Approach: Applied Mathematics Formula for Prevent Discrimination - Iriyadi, Deni; Rustam, Ahmad; Hartati, Hevriana (Universitas Muhammadiyah Mataram, 2024)
This study aims to determine the accuracy of the equating method that uses a circle equation approach in terms of its circular arc (Simplified Circle Arc). This research uses 2015 National Examination data from two questions packages. Using the number of preliminary samples as many as 2135 on the X and 2271 test devices on the Y test. After doing a Rasch analysis using a Mean Square Outfit (MNSQ), the data was acquired and analyzed. Following this, replication was performed up to a maximum of 50 times for each kind of data distribution. For each replication, up to a maximum of 50 respondents were selected from the original data set to be used as data for score equalization. The Root Mean Square Error (RMSE) statistic is then used to analyze the outcomes of the equating score. The results showed that the average RMSE group that has the same distribution will provide a lower RMSE value compared to groups that have different data distributions. The low average RMSE value indicates the accuracy of the equal of the scores performed. Thus, the use of the SCA method is highly recommended to equalize scores, especially in small samples in classes at school to prevent discrimination in grading.